2005
DOI: 10.1523/jneurosci.3066-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Voltage-Gated Sodium Channel β2 Subunit in Neuropathic Pain Models: Characterization of Expression in Injured and Non-Injured Primary Sensory Neurons

Abstract: The development of abnormal primary sensory neuron excitability and neuropathic pain symptoms after peripheral nerve injury is associated with altered expression of voltage-gated sodium channels (VGSCs) and a modification of sodium currents. To investigate whether the ␤2 subunit of VGSCs participates in the generation of neuropathic pain, we used the spared nerve injury (SNI) model in rats to examine ␤2 subunit expression in selectively injured (tibial and common peroneal nerves) and uninjured (sural nerve) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 68 publications
6
98
0
3
Order By: Relevance
“…These can be at multiple sites along the axons, including distal terminals. Evidence from earlier studies has implicated multiple sites in the generation of ectopic activity, including peripheral nerve terminals (Albrecht et al, 2006;Kauppila et al, 2002;Pare et al, 2007), at the site of nerve injury (Bird et al, 2007;Coward et al, 2000;Devor et al, 1993;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Tal and Eliav, 1996), along the nerve (Amir et al, 2005;Gold et al, 2003;Pertin et al, 2005), adjacent nerves (Sotgiu et al, 2006), and in the dorsal root ganglia (Amir et al, 1999;Chaplan et al, 2003;Craner et al, 2002;Liu et al, 2000bLiu et al, , 2002Michaelis et al, 2000;Na et al, 2000;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Study and Kral, 1996;Xie et al, 1995).…”
Section: Site Of Generation Of Peripheral Drivementioning
confidence: 99%
See 1 more Smart Citation
“…These can be at multiple sites along the axons, including distal terminals. Evidence from earlier studies has implicated multiple sites in the generation of ectopic activity, including peripheral nerve terminals (Albrecht et al, 2006;Kauppila et al, 2002;Pare et al, 2007), at the site of nerve injury (Bird et al, 2007;Coward et al, 2000;Devor et al, 1993;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Tal and Eliav, 1996), along the nerve (Amir et al, 2005;Gold et al, 2003;Pertin et al, 2005), adjacent nerves (Sotgiu et al, 2006), and in the dorsal root ganglia (Amir et al, 1999;Chaplan et al, 2003;Craner et al, 2002;Liu et al, 2000bLiu et al, , 2002Michaelis et al, 2000;Na et al, 2000;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Study and Kral, 1996;Xie et al, 1995).…”
Section: Site Of Generation Of Peripheral Drivementioning
confidence: 99%
“…Another view suggests that mechanisms at the spinal dorsal horn level require continuous facilitatory input from supraspinal structures Carlson et al, 2007;Gardell et al, 2003;Kauppila et al,1998;Kovelowski et al, 2000;Ossipov et al, 2000;Pertovaara et al, 1997Pertovaara et al, , 2001Porreca et al, 2001;Saade et al, 2006aSaade et al, ,b, 2007Suzuki et al, 2002Suzuki et al, , 2004aVeraPortocarrero et al, 2006). However, in both animal models and humans effects of peripheral neuropathy including peripheral neurodegeneration, altered Na + and K + ion channel expression (Coward et al, 2001a,b;Hong et al, 2004;Hong and Wiley, 2006;Joshi et al, 2006;Matthews et al, 2006;Shembalkar et al, 2001), and abnormal impulse discharge (Nordin et al, 1984;Nystrom and Hagbarth, 1981) in sensory afferents have been shown to persist several weeks/months (Casula et al, 2004;Coward et al, 2000;Fried et al, 1991;Kretschmer et al, 2002;Pan et al, 2001;Pertin et al, 2005;Roytta et al, 1999;Seltzer et al, 1991b). This raises the question what role, if any, do such multiple and long lasting modifications in peripheral sensory input play in maintaining the persistent changes in the central nervous system and in neuropathic pain?…”
Section: Introductionmentioning
confidence: 99%
“…In rat models for neuronal injuries of various peripheral afferent neurons, Pertin et al (43) demonstrated that sodium channel β 2 -subunit protein level was increased in cell bodies and peripheral axons of injured neurons and neighboring non-injured neurons, with no increase of sodium channel β 2 -subunit mRNA level. The authors speculated that neuronal injury-induced upregulation of β 2 -subunit protein may be attributed to the promotion of β 2 -subunit mRNA translation and/ or the retardation of proteolytic degradation of β 2 -subunit protein.…”
Section: Sodium Channel Remodeling In Pain: Inflammation Diabetic Nementioning
confidence: 99%
“…Distinctly, the extracellular domain of β-subunit contains a single immunoglobulin V-set fold structure, that enables the β-subunit to interact with cell adhesion molecules (e.g., neurofascin), extracellular matrix proteins (e.g., tenascin), and intracellular scaffold proteins (e.g., ankyrin) (39,40). In this context, it should be noted that expressions studies indicate that β-subunits regulate gating kinetics and cell surface density of sodium channels (39,40,43).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the pore-forming -subunit, 2 subunit was reported to be up-regulated in injured and non-injured sensory neurons after peripheral nerve injuries (Pertin et al, 2005) and the development of spared nerve injury-induced mechanical allodynia is attenuated in 2-null mice (Lopez-Santiago et al, 2006), suggesting the important role of 2 subunit in NINP. The 7 involvement of Na + channel 2 subunit in neuropathic and inflammatory pain has been extensively reviewed (Brackenbury & Isom, 2008).…”
Section: Voltage-gated Namentioning
confidence: 99%